Where to now? Searching beyond Medline. (2nd February 2021) - Holland, Matt; Dutton, Michelle; Glover, Steve
Abstract : This article looks at the tools available to you to extend your search beyond the major bibliographic sources. The article identifies the type of literature you can find and which tools are suitable to use to find them. It aims to help you to broaden the scope of your search to find more relevant material. There is a warning about predatory journals and the need to take a critical approach to material that has not been peer-reviewed.